2022
DOI: 10.3390/cancers14215356
|View full text |Cite
|
Sign up to set email alerts
|

Patients Regret Their Choice of Therapy Significantly Less Frequently after Robot-Assisted Radical Prostatectomy as Opposed to Open Radical Prostatectomy: Patient-Reported Results of the Multicenter Cross-Sectional IMPROVE Study

Abstract: Patient’s regret (PatR) concerning the choice of therapy represents a crucial endpoint for treatment evaluation after radical prostatectomy (RP) for prostate cancer (PCA). This study aims to compare PatR following robot-assisted (RARP) and open surgical approach (ORP). A survey comprising perioperative-functional criteria was sent to 1000 patients in 20 German centers at a median of 15 months after RP. Surgery-related items were collected from participating centers. To calculate PatR differences between approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
(73 reference statements)
1
3
1
Order By: Relevance
“…The proportion of RARP increased to 85% in the United States in 2013, 1 93% in England in 2018, 2 and 65% in Australia in 2019 3 . Similar trends have been observed in other advanced economies 4–6 …”
Section: Figsupporting
confidence: 65%
See 1 more Smart Citation
“…The proportion of RARP increased to 85% in the United States in 2013, 1 93% in England in 2018, 2 and 65% in Australia in 2019 3 . Similar trends have been observed in other advanced economies 4–6 …”
Section: Figsupporting
confidence: 65%
“…3 Similar trends have been observed in other advanced economies. [4][5][6] North Shore Hospital is the only public hospital in Aotearoa New Zealand (AoNZ) with a da Vinci Surgical System (dVSS) (Intuitive Surgical, Sunnyvale, California, USA), and its first RARP was performed in late 2021. Figure 1 outlines the trends for prostatectomy and new prostate cancer registrations in AoNZ from 2010 to 2020 using anonymous procedure-only data from the AoNZ distributor of the dVSS (Device Technologies, Auckland, New Zealand), the National Minimum Dataset for hospital events (National Collections and Reporting, Manat u Hauora, Ministry of Health) and publicly available new prostate cancer registrations from the New Zealand Cancer Registry.…”
mentioning
confidence: 99%
“…SUI is a highly important outcome parameter for patients' quality of life after RP. Our study group has previously demonstrated an association between SUI and a threefold increased presence of critical DR after RP [25]. While no significant difference in postoperative SUI was observed between CCs and nCCs in the current study, patients who underwent RARP experienced significantly less SUI (OR 0.39; p < 0.001) compared to those treated with ORP or LRP.…”
Section: Comparison Of Certified and Noncertifiedcontrasting
confidence: 62%
“…These include the establishment of a structured network among specialized departments, transferring doctors, encounter groups, and the clinic. Additionally, supportive measures such as psycho-oncological support, outreach services, and rehabilitation programs must be provided for the patients [21]. To enhance surgical outcomes, oncological criteria such as the annual caseload of RPs, PSM rate, and NS rate are evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 20 urological clinics in Germany were requested to report data of their most recent consecutive 50 radical prostatectomies in 2021 (in addition to clinical and histopathological criteria, demographic and functional aspects of patients were assessed using a questionnaire). [3][4][5] Among the initially contacted 1,000 patients, a response rate of 75% was achieved.…”
mentioning
confidence: 97%